On features of the radiation from pulsed discharges initiated by thick wires in water - Fedorovich, O.A.; Voitenko, L.M. (Вопросы атомной науки и техники, 2015)
The investigation results on the distribution of the plasma channel radiance intensity in the visible spectral region are reported. The pulsed discharge in water is initiated by the Tungsten wire (Ø 300 μm) explosion under initial battery voltage of 20 kV. The plasma channel radiance intensity does not correlate with the power contribution into the plasma. The energy contribution ceases at 20 μs, and the maximum radiation of the continuous spectrum is observed at 80 μs. The radiation intensity is practically constant between 50 and 120°up to the basic state. It is not succeeded to record the intensity (Тn ≤ 6·10³ К) in the interval to 20 μs. The dynamics in time of the absorption line spectrum in the region between 490…560 nm, explaining the radiation intensity increase with time, is investigated. The visible radiation region comprises a wave length band corresponding to the plasma frequency in the channel. In the course of time, the plasma frequency band displaces into the red spectral region and the radiation intensity in the violet region increases to the values corresponding to Т = 2·10⁴ К. The radiation reflection from the channel boundary at the plasma frequency takes place. The time dependence of the pressure obtained from the experimental hydrodynamic calculation results has been compared with the adiabatic curve. A significant difference between results is evident. The same calculation for the temperature change shows that at the initial discharge stage T= 3·10⁴ К should be reached. The radiation spectrum dynamics in the region between 620 and 700 nm is shown. In the Нα line region (656.3 nm) neither the absorption line nor the radiation line are observed in the spectrum up to 83 μm. Приводятся результаты исследований распределения интенсивности (I) излучения плазменного канала в видимом диапазоне. Канал импульсного разряда в воде инициируется взрывом проводника из W диаметром 300 мкм при начальном напряжении на батарее 20 кВ. I свечения поверхности канала не коррелирует с вкладом мощности в плазму. Вклад энергии заканчивается на 20 мкс, а максимум излучения сплошного спектра наблюдается на 80 мкс. I излучения практически не меняется в интервале времени от 50 до 120 мкс. Происходит «нереализация» уровней линейчатого спектра W вплоть до основного состояния. До 20 мкс излучение не удается зарегистрировать (Тя ≤ 6·10³ К). Изучена динамика спектра линий поглощения во времени на участке спектра 490…560 нм, объясняющая увеличение интенсивности излучения с течением времени. В видимый диапазон излучения попадает область длин волн, соответствующая плазменной частоте. С течением времени наблюдается смещение области плазменной частоты в красную часть спектра и увеличение интенсивности излучения в фиолетовой области до значений, соответствующих Т = 2·10⁴ К. Происходит отражение излучения от границы канала на плазменной частоте. Проведено сравнение временной зависимости давления, полученного из расчетов по экспериментальным гидродинамическим данным и по адиабате. Видно сильное расхождение результатов. Такой же расчет для изменения Т показывает, что на начальной стадии разряда Т должна достигать значений 3·10⁴ К. Приведена динамика спектра излучения в области 620…700 нм. В области линии Нα (656,3 нм) до 83 мкм в спектре не наблюдаются линии ни поглощения, ни излучения. Наводяться результати досліджень розподілу інтенсивності (I) випромінювання плазмового каналу у видимому діапазоні. Канал імпульсного розряду у воді ініціюється вибухом провідника з W діаметром 300 мкм при початковій напрузі на батареї 20 кВ. I випромінювання поверхні каналу не корелює з вкладом потужності в плазму. Вклад енергії закінчується на 20 мкс, а максимум випромінювання суцільного спектра спостерігається на 80 мкс. I випромінювання практично не змінюється в інтервалі часу від 50 до 120 мкс. Відбувається «нереалізація» рівнів лінійчатого спектра W аж до основного стану. До 20 мкс випромінювання не вдається зареєструвати (Тя ≤ 6·10³ К). Вивчена динаміка спектра ліній поглинання в часі на ділянці спектра 490…560 нм, що пояснює збільшення інтенсивності випромінювання з часом. У видимий діапазон випромінювання потрапляє область довжин хвиль, яка відповідає плазмовій частоті. З плином часу спостерігається зміщення області плазмової частоти в червону частину спектра і збільшення інтенсивності випромінювання в фіолетовій області до значень, відповідних Т = 2·10⁴ К. Відбувається відбиття випромінювання від кордону каналу на плазмовій частоті. Проведено порівняння часової залежності тиску, отриманого з розрахунків за експериментальними гідродинамічними даними і по адіабаті. Видно сильну розбіжність результатів. Такий же розрахунок для зміни Т показує, що на початковій стадії розряду Т повинна досягати значень 3·10⁴ К. Наведено динаміку спектра випромінювання в області 620…700 нм. В області спектра лінії Нα (656,3 нм) до 83 мкм не спостерігаються лінії ні поглинання, ні випромінювання.